Comprehension monitoring strategies as determinants of achievement in reading comprehension of secondary school students with learning disabilities in Ibadan, Oyo state (2019)
This study examined three comprehension monitoring strategies: rereading, clarifying concepts and vocabulary in texts and reflecting/reviewing text as determinants of achievement in reading comprehension among secondary school students with learning disabilities in Ibadan, Oyo State. The study adopted the correlation research design. Purposive sampling was used in selecting200 male and female Junior Secondary School One (JSS1) students with learning disabilities in Ibadan. Data were collected using three instruments: Pupil Rating Scale, Questionnaire on Comprehension Monitoring Strategies and Reading Comprehension Evaluative Scale. Pearson Product Moment Correlation and Multiple Regression Analysis were used to analyse the data obtained at p<0.05. The results showed that the three independent variables (rereading; clarifying concepts and vocabulary in the text; and reflecting and reviewing the text) positively correlated with the dependent variable (achievement in reading comprehension of students with learning disabilities): rereading (r= 0.574) clarifying concepts and vocabulary (r- 0.450) reflecting/reviewing (r =0.609). However, it was found that reflecting/reviewing text made the highest contribution (β=.636, t=13.312) followed by rereading with β=.390, t=6.510, while clarifying concepts and vocabulary in text had the least contribution (β =.347, t=6.561) to the explanation of students' achievement in reading comprehension. By implication, the study recommended that an increased influence of the three independent variables could predict or lead to increase in achievement in reading comprehension. On the basis of the findings, it was recommended that teachers of students with learning disabilities should encourage the students to implement the metacognitive comprehension monitoring strategies of rereading, clarifying concepts and vocabulary in text and reflecting and reviewing the text.